THE RELATIONSHIP OF CUSTOMS, KNOWLEDGE AND AFFORDABILITY OF FACILITIES AND INFRASTRUCTURE TO AID SELECTIONS LABOR - Mujahidah Nurhama; Nanik Yuliwati (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction: Indonesia is aggressively targeting reducing the maternal mortality rate to 70 deaths per 100 thousand live births by 2030. Currently, the proportion of maternal deaths is approximately 305 deaths per 100 thousand live births. Where the biggest deaths occur in hospitals around 77%. The mother could not be saved, for one thing, because the mother who was referred to the hospital was already in a state of severe complications. This happens because identification and examination during pregnancy are not optimal and must be strengthened (RI Ministry of Health, 2021). Purpose of Writing: The purpose of this writing is to find out cultural relations, affordability of facilities and infrastructure and mothers' perceptions of the behavior of choosing delivery assistance in the working area of the Cisimeut Health Center in 2022. The sample in the study was 42 mothers who had given birth in January-December 2022. Research Method : This research method is descriptive analytic, namely research that tries to explore how and why the phenomenon occurs, then analyzes the dynamics of the correlation between these phenomena. Research Results: there is no significant relationship between Culture or Customs and Choice of Birth Assistance Behavior in the Work Area of the Cisimeut Health Center in 2022 Continuity Correction value p = 0.478 means that p value ≥ 0.05, there is a relationship between affordability of facilities (Continuity Correction value p = 0.023) , knowledge (Continuity Correction value p = 0.001) on the behavior of choosing delivery assistance in the Work Area of the Cisimeut Health Center in 2022 Conclusions and Suggestions: There is no significant relationship between culture and behavior in choosing delivery assistance in the working area of the Cisimeut Health Center in 2022.